Pengaruh Penggunaan Asbuton LGA B50/30 Terhadap Sifat Campuran Laston AC-WC - Faizal, Faizal; Nurdin, Abdul Rahim; Mallawangeng, Tamrin (Jurnal Penelitian Teknik Sipil Konsolidasi, 2025)
The use of Asbuton B50/30 in Asphalt Concrete-Wearing Course (laston) mixtures represents an intriguing innovation in road construction. This study aims to evaluate the impact of Asbuton B50/30 on the quality of laston mixtures, focusing on strength, cohesion, thermal stability, viscosity, and the potential for utilizing local resources. The experimental method includes a series of laboratory and field tests to examine various laston compositions with Asbuton B50/30. Results indicate that adding Asbuton B50/30 significantly improves structural strength and material stiffness, as well as cohesion between mix components and thermal stability. However, changes in asphalt viscosity and the implications for local material usage should also be considered, as they can affect costs and resource efficiency. These findings provide valuable insights for infrastructure development, particularly in considering Asbuton B50/30 as an alternative for Asphalt Concrete-Wearing Course mixtures. Utilizing Asbuton B50/30 has the potential not only to enhance road performance and durability but also to support sustainability by maximizing local resources, making it an appealing choice for the road construction industry in the future.